The Analysis of Factors Influencing Carbon Emissions in Sichuan Province - Bi, Shuning; Zhou, Bingji; Chen, Xi (International Journal of Natural Resources and Environmental Studies, 2024)
Based on the population, economic development level, urbanization rate, industrial structure, energy intensity, government expenditure, and foreign trade of Sichuan Province from 2000 to 2020, an improved STIRPAT model is constructed. Ridge regression estimation method is employed to analyze the relationship between carbon emissions and various influencing factors. The research findings indicate that there is a positive correlation between economic development level, urbanization rate, industrial structure, government expenditure, and foreign trade, and carbon emissions in Sichuan Province, but the degree of influence varies for each factor. Among them, industrial structure, namely the proportion of secondary industry, has the greatest impact, while energy intensity shows a negative correlation with carbon emissions. Finally, considering the above analysis, measures for emissions reduction such as fostering a clean and low-carbon industrial system and promoting technological innovation in the low-carbon sector are proposed.